If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = 60x + 259240 Reorder the terms: x = 259240 + 60x Solving x = 259240 + 60x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-60x' to each side of the equation. x + -60x = 259240 + 60x + -60x Combine like terms: x + -60x = -59x -59x = 259240 + 60x + -60x Combine like terms: 60x + -60x = 0 -59x = 259240 + 0 -59x = 259240 Divide each side by '-59'. x = -4393.898305 Simplifying x = -4393.898305
| 12+4(z-3)=-5z+5 | | 1.4(z+0.5)=0.7(z-13) | | 3/2c+4=15 | | 5x^2+28+15=0 | | (-20/30)27/30 | | -5x-19=-13 | | 5*3/4*1/3 | | 2x(-3)=6 | | 7b/4+5=54 | | 12-2(7+2t)=2(t-1) | | 5x^2=42x+27 | | 3y+x=-16 | | 3y+x=-16 | | (4x-5)/(3x+7) | | 4(4-8y)-y=3y+7 | | 2/3c+4=15 | | f(x)=-3 | | 8=3c-7 | | 3x+1/4=4x+3/4 | | 2x^2-27x+168=0 | | 3y+14=5y | | 10x+9=3(3x+2) | | x^4-10x^2+40=0 | | U-3/u-2=4/u+4 | | 59x=-2-1+3 | | v+5/6v-1/6=(3/8v+1/4) | | -6(n+2)+13=-3n-8 | | 5g+11=-3 | | -2x+10-4=6 | | 2x^3+27=0 | | 2/3x-1/4+4/3x+3/4=6 | | 2(5c-1)-5=(8c+5) |